Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Daya Saing Industri Kuliner di Bali - I Wayan Eka Sudarmawan; I Made Hadi Purnantara; Kadek Wira Adi Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
The Balinese culinary industry, which is the backbone of the regional economy, faces various problems that hinder its competitiveness, such as a lack of human resource skills, low service quality, and limited product innovation. Increasingly fierce competition from local and international business actors exacerbates this problem. High employee turnover rates are also a constraint, resulting in the loss of expertise and training investments. The situation is worsened by a lack of understanding of the importance of effective and efficient human resource management (HRM) in managing quality human resources. Therefore, this research is important to conduct in order to find appropriate and efficient HRM strategies to improve the competitiveness of the Balinese culinary industry. This research uses a qualitative approach with a case study method, involving in-depth interviews with culinary business actors in Bali, document analysis, and field observations. The research is expected to provide recommendations for broad human resource (HR) strategies, which include employee training and development as well as efficient recruitment and selection systems, and the development of a positive and innovative work culture. These recommendations aim to improve the quality of human resources, increase productivity, and ultimately increase the competitiveness of the Balinese culinary industry in domestic and international markets.